The government R&D funding and management performance: The mediating effect of technology innovation - Seunghoo Jin; Kangwon Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Korea's small- and medium-sized enterprises are desperate to improve their performance through engaging in technological innovation, due to the fierce competition prevalent in a low growth economic environment. However, most small- and medium-sized enterprises are having difficulty responding to changes in the economic environment due to the challenge of developing their own technologies and their limited resources. The aim of this study is to assess whether government financial support for R&D aimed at small- and medium-sized enterprises has contributed to improvements in their business management performance. The sample of this study was comprised of 105 KOSDAQ-listed small- and medium-sized enterprises with experience in technology development. The empirical analysis was conducted on the basis of the mediating effect measurement method of Baron and Kenny (1986). It was found that company technological innovation capabilities have a positive effect on management performance, and in particular, that the majority of companies that received government financial support for R&D have improved their management performance. Therefore, it is recommended that small- and medium-sized companies take an active part in various government R&D financial support programs and make efforts to strengthen their technological innovation in areas such as their product service and process innovation capabilities.
Keywords: 650; technological innovation capability; mediating effects; R&D funds